Signs of Urban Evolution? Morpho-Functional Traits Co-variation Along a Nature-Urban Gradient in a Chagas Disease Vector - Montes de Oca-Aguilar, Ana C.; González-Martínez, Adriana; Chan-González, Raúl; Ibarra-López, Pilar; Smith-Ávila, Selene; Córdoba-Aguilar, Alex; Ibarra-Cerdeña, Carlos N. (Frontiers in Ecology and Evolution, 2022)
Environmental change (i.e. urbanization, etc.) impacts species in contrasting ways, with some species experiencing benefits due to their way of life (i.e. blood-sucking insects). How these species respond to such change is not well understood and for species involved in human diseases, this “how” question is particularly important. Most Triatominae bug species, inhabit tropical and subtropical forests where their vertebrate hosts’ temporal abundance depends on climate seasonality. However, in human encroached landscapes, triatomines can benefit of resource stability leading to adaptive phenotypic change to track novel hosts. We tested for an association between different landscapes and morpho-functional traits linked to sensory, motion, and feeding functions in Triatoma dimidiata and compare fertility (i. e. number of eggs) in each landscape as a measure of fitness. Using geometric and traditional morphometric tools, we predicted that traits will show a morphological simplification in bugs present in urbanized areas. While wing morphology or proboscis were not influenced by landscape class, the opposite occurred for thorax morphology and number of sensilla. As such, wing and thorax morphology did not covariate under modified landscape scenarios, but we detected a morpho-functional convergence for thorax size and antennal phenotype, in both sexes, with a simplification trend, from nature to urban settings. We detected a negligible fitness cost in the urban landscape. The convergence of the thorax size and antennal phenotype suggests differences in flight/locomotion performance and host/environment perception, as a possible adaptive response to a release of the selective pressures of its native habitat. These results imply that this vector species has adapted to urbanized areas.